Trend and Impact of Public Debt in Nepalese Economy - Sharma, Yadab Raj (Academic Voices: A Multidisciplinary Journal, 2015)
The public debt or public borrowing in Nepal is considered to be an important source of income of the government. Public debt helps to achieve targeted economic growth and to narrow down the gap between expenditure and revenue. However, the country is falling into debt trap in the form of interest and principal payment. In this article an attempt has been made to find out the situation, trend and impact of public debt on Nepalese economy. DOI: http://dx.doi.org/10.3126/av.v4i0.12363 Academic Voices Vol.4 2014: 85-89